Sardjito score accuracy value in enforcing COVID-19 diagnosis in surgical patients in General Hospital dr. Zainoel Abidin Banda Aceh - Yudi Nugraha; Safrizal Rahman; Jufriady Ismy (Journal of International Surgery and Clinical Medicine, 2021)
Background: SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) is a virus with a positive chain of RNA (RiboNucleic Acid) This viral infection spread rapidly with subsequent human-to-human transmission and increase in the number of cases in other countries around the world. Aceh is one of the areas affected by COVID-19 in Indonesia. Despite the need for fast and precise diagnostics, facilities capable of carrying out RT-PCR are still limited in some places. This study aims to determine the accuracy of the Sardjito score in establishing the diagnosis of Covid 19 in surgical patients.. Methods: Consecutive sampling is included in the non-probability sampling technique where all subjects who come sequentially will be used as research samples until the required number of samples is met. The data obtained will be presented using tables and curves. For the analysis of the data results, the Spearman-Pearson correlation test was carried out, and for the correlation between the Sardjito Score and the PCR swab results, it was continued by analyzing the sensitivity and specificity values. Results: Based on the cross tabulation, it shows that the majority of patients' Sardjito scores are moderate probability. Research subjects with moderate probability and negative PCR results were 83 people (91.2%). The specificity of the Sardjito score is 87% compared to the PCR results. In addition, the positive predictive value of 62%. While the negative predictive value of 96%. Conclusions: This Sardjito Score can be used as a tool for COVID-19 diagnostic tests.